Implementasi perangkat pembelajaran menggunakan inkuiri terbimbing terhadap aktivitas belajar siswa pada materi struktur dan fungsi jaringan tumbuhan di SMP Negeri 12 Gorontalo kelas VIII - Bulowe, Yuniarty R; Yusuf, Frida Maryati; Kandowangko, Novri Youla (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
This research is a quantitative descriptive study with a pre-experimental design which is intended to increase student learning activities through the implementation of guided inquiry-based learning on the structure and function of plant tissue materials. This research was conducted at SMP Negeri 12 Gorontalo class VIII for 4 meetings. The target of this research is students of class VIII-2 SMP Negeri 12 Gorontalo with a total of 28 students, Odd Semester in the 2019/2020 Academic Year. Student activities are measured through student activity observation sheets, then analyzed, grouped and presented through tables. The results of this study indicate that the implementation of guided inquiry-based learning tools can improve student learning activities on the structure and function of plant tissue in class VIII-2 of SMP Negeri 12 Gorontalo. The increase in student learning activities can be seen from the aspects observed at each meeting, namely meeting 1 the highest score in aspect 1 reaches a percentage value of 100, the lowest score in aspects 2 and 8 reaches a percentage value of 66. Meeting 2 the highest scores in aspects 1 and 4 reach a value percentage 95, the lowest score in aspect 2 with a percentage value of 76. Meeting 3 the highest values in aspects 1, 4 and 5 reached a percentage value of 100, the lowest value was in aspect 10 with a percentage value of 78. The meeting of 4 highest scores was in aspects 1, 3, 4 and 5 reaches a percentage value of 100, the lowest value in aspect 11 with a percentage value of 81.